Modification of interface states and series resistance properties of Al/p-type Si Schottky diode with HF chemical treatment - Al-Ghamdi, A. A.; Al-Hartomy, Omar A.; Cavas, M.; El-Tantawy, Farid; Yakuphanoğlu, Fahrettin (Natl Inst Optoelectronics, 2012)
The Al/p-type Si Schottky diode was fabricated with chemical treatment to modify its interface states and series resistance properties. The barrier height, ideality factor and series resistance parameters of the diode were determined by performing Cheung plots. The barrier height, ideality factor and series resistance values of the diode were found to be 0.67 eV, 1.65 and 4.93 k Omega, respectively. The passivaiton of the surface of the silicon increases the value of Schottky barrier height. The barrier height of the studied diode is higher than that of conventional Al/p-Si diodes. The ideality factor higher unity may be attributed to the chemical oxide layer grown on the semiconductor. The density of the interface states without series resistance is higher than that of with series resistance. It is evaluated that the series resistance value should be taken into account in determining the interface state density distribution. The density of interface states of the diode studied is of the order of 1.93x10(13) eV(-1)cm(-2). The obtained results indicate that HF chemical treatment modifies the interface states and series resistance properties of Al/p-Si Schottky diode.
Keywords: Schottky diode; Interfacial state density; Series resistance